2006
DOI: 10.1002/dvdy.20665
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression profiles of Xenopus laevis reference genes

Abstract: Cell differentiation depends mainly on specific mRNA expression. To quantify the expression of a particular gene, the normalisation with respect to the expression of a reference gene is carried out. This is based on the assumption that the expression of the reference gene is constant during development, in different cells or tissues or after treatment. Xenopus laevis studies have frequently used eEF-1 alpha, GAPDH, ODC, L8, and H4 as reference genes. The aim of this work was to examine, by real-time RT-PCR, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 17 publications
3
37
0
2
Order By: Relevance
“…The quantification of total RNA profile presented here complements and correlates the partial quantification data previously published [20]. A light decrease of the concentration of total RNA was observed at stage 11 (gastrula) and was positively associated with a maternal cell death program which is set up at fertilization and abruptly activated at the onset of gastrulation (10.5) [21].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The quantification of total RNA profile presented here complements and correlates the partial quantification data previously published [20]. A light decrease of the concentration of total RNA was observed at stage 11 (gastrula) and was positively associated with a maternal cell death program which is set up at fertilization and abruptly activated at the onset of gastrulation (10.5) [21].…”
Section: Discussionsupporting
confidence: 80%
“…The RT-qPCR normalization of mRNA expression patterns to reference genes such as ODC, GAPDH, EF-1α, H4 or L8, widely used in Xenopus RT-qPCR experiments, is not particulary suitable, because their levels vary during Xenopus development. The normalization to total RNAs is more appropriate [20]. Therefore, the mRNA expression profiles of CAPN8b and CAPN1 (mu/I) in stage series were normalized to total RNA of each embryonic stage and to stage 0, and are presented in arbitrary units.…”
Section: Discussionmentioning
confidence: 99%
“…For each study, a minimum of three PCR reactions was performed using at least two cDNA samples obtained in independent experiments. The following primers and conditions were used in PCR amplifications: EF1␣, primer sequences as described previously (Sindelka et al, 2006), 26 cycles, annealing temperature (T a ) of 56°C; sema3A-F, GenBank accession number NM_001085855.1, nucleotides 611-631, and sema3A-R, nucleotides 1596 -1616, 30 cycles, T a ϭ 58°C; slit1-F, GenBank accession number NM_001087109, nucleotides 3309 -3329, and slit1-R, nucleotides 3511-3531, 35 cycles, T a ϭ 56°C. Densitometric analyses of reverse transcription (RT)-PCR results were obtained using the public domain NIH ImageJ software version 1.40g.…”
Section: Methodsmentioning
confidence: 99%
“…It is unclear whether rpl8 expression is stable during embryonic development of R. nigromaculata. Recently, several studies reported that rpl8 expression was not stable in X. laevis and X. tropicalis during embryogenesis, suggesting that rpl8 is unsuitable as a reference gene for analyzing gene expression in this developmental period of this amphibian species by qRT-PCR (Dhorne-Pollet et al, 2013;Sindelka et al, 2006). In the literature, in fact, many researchers used rpl8 as the reference gene for analyzing gene expression in X. laevis and X. tropicalis during embryonic development (Langlois et al, 2010;Morvan-Dubois et al, 2008).…”
Section: Discussionmentioning
confidence: 99%